Managing diabetic patients with moderate or severe renal impairment using DPP-4 inhibitors: focus on vildagliptin - Russo E (Dove Medical Press, 2013)
Eleonora Russo, Giuseppe Penno, Stefano Del Prato Department of Clinical and Experimental Medicine, Section of Diabetes and Metabolic Disease, Azienda Ospedaliero Universitaria di Pisa, and University of Pisa, Pisa, Italy Background: Dipeptidyl peptidase-4 (DPP-4) inhibitors are novel classified oral anti-diabetic drugs for the treatment of type 2 diabetes mellitus (T2DM) that provide important reduction in glycated hemoglobin, with a low risk for hypoglycemia and no weight gain. In T2DM patients with reduced renal function, adequate glycemic control is essential to delay the progress of kidney dysfunction, but they are at a greater risk of experiencing hypoglycemic events, especially with longer-acting sulfonylureas and meglitinides. Objective: To evaluate vildagliptin as an option to achieve glycemic control in T2DM patients with moderate or severe chronic kidney disease (CKD). Methods: A comprehensive search in the literature was performed using the term "vildagliptin." Original articles and reviews exploring our topic were carefully selected. Results: Vildagliptin provides effective glycemic control in patients with T2DM and CKD. Dose reductions are required for vildagliptin and other DPP-4 inhibitors, except linagliptin, in T2DM patients with moderate-to-severe CKD. Dose of vildagliptin had to be reduced by half (to 50 mg/day) both for moderate (estimated glomerular filtration rate [eGFR] ≥30 to ≤50 mL/min) and severe CKD (eGFR < 30 mL/min). Available results support a favorable efficacy, safety, and tolerability profile for vildagliptin in T2DM with moderate or severe renal failure. Preliminary data may suggest additional benefits beyond improvement of glycemic control. Conclusion: Vildagliptin can be safely used in T2DM patients with varying degrees of renal impairment. Dose adjustments for renal impairment are required. Potential long-term renal benefit of vildagliptin needs to be further explored. Keywords: type 2 diabetes mellitus, renal function, chronic kidney disease